The Hibernian Cosmopolis: The Modernities of James Joyce's Ulysses and Don DeLillo's Late Novels - Howlett, Adrian Neville (Trinity College Dublin. School of English. Discipline of English, 2022)
This thesis provides a comparative study of James Joyce's Ulysses with Don DeLillo's late novels. This comparison examines economics, time and technology in the work of both writers to create a picture of two different modernities: Joyce's vision of modernity in development and DeLillo's depiction of a pressurised modernity that is reaching its breaking point. Despite the clear historical differences between the two writers and concomitant time periods, consonances may also be found, chiefly in the fact that for both, modernity compromises a knot of financialisation, temporal compression and technological development. The undecidability of determining which of these factors drives the advance of modernity is a crucial strand to understanding the work of Joyce and DeLillo alike; this thesis argues that this undecidability is in fact a defining feature of modernity. Within a literary context, the comparative study effected in this thesis also allows a dialogue to be enacted between modernists like Joyce and their antecedents, sometimes gathered under the rubric postmodernism , like DeLillo. DeLillo's persistent references to modernist literature, as well as his ekphrastic impulses, usually in reference to contemporary art, provide a conscious gaze back towards literary modernism, connecting these periods in art as well as in their shifting concepts of modernity.
APPROVED
Keywords: James Joyce; Don DeLillo; modernity; modernism; postmodernity; postmodernism; late capitalism; literature and technology; literature and economics; literature and temporality; neoliberalism